Numerical Simulation and Kalman-based Control of a Hall Thruster for CubeSats - Marques Costa, Hudson; Andres Miranda Cerda, Rodrigo; Leonardo Ferreira, José; Maurício Muñoz Arboleda, Daniel (Revista Interdisciplinar de Pesquisa em Engenharia, 2025)
<div class="intersub-ai-chat" style="color-scheme: initial; forced-color-adjust: initial; mask: initial; math-depth: initial; position: fixed !important; position-anchor: initial; text-size-adjust: initial; appearance: initial; color: initial; font: initial; font-palette: initial; font-synthesis: initial; position-area: initial; text-orientation: initial; text-rendering: initial; text-spacing-trim: initial; -webkit-font-smoothing: initial; -webkit-locale: initial; -webkit-text-orientation: initial; -webkit-writing-mode: initial; writing-mode: initial; zoom: initial; accent-color: initial; place-content: initial; place-items: initial; place-self: initial; alignment-baseline: initial; anchor-name: initial; anchor-scope: initial; animation-composition: initial; animation: initial; app-region: initial; aspect-ratio: initial; backdrop-filter: initial; backface-visibility: initial; background: initial; background-blend-mode: initial; baseline-shift: initial; baseline-source: initial; block-size: initial; border-block: initial; border: initial; border-radius: initial; border-collapse: initial; border-end-end-radius: initial; border-end-start-radius: initial; border-inline: initial; border-start-end-radius: initial; border-start-start-radius: initial; bottom: 0px !important; box-decoration-break: initial; box-shadow: initial; box-sizing: border-box; break-after: initial; break-before: initial; break-inside: initial; buffered-rendering: initial; caption-side: initial; caret-animation: initial; caret-color: initial; clear: initial; clip: initial; clip-path: initial; clip-rule: initial; color-interpolation: initial; color-interpolation-filters: initial; color-rendering: initial; columns: initial; column-fill: initial; gap: initial; column-rule: initial; column-span: initial; contain: initial; contain-intrinsic-block-size: initial; contain-intrinsic-size: initial; contain-intrinsic-inline-size: initial; container: initial; content: initial; content-visibility: initial; corner-shape: initial; corner-block-end-shape: initial; corner-block-start-shape: initial; counter-increment: initial; counter-reset: initial; counter-set: initial; cursor: initial; cx: initial; cy: initial; d: initial; display: flex !important; dominant-baseline: initial; dynamic-range-limit: initial; empty-cells: initial; field-sizing: initial; fill: initial; fill-opacity: initial; fill-rule: initial; filter: initial; flex: initial; flex-direction: column !important; flex-wrap: initial; float: initial; flood-color: initial; flood-opacity: initial; grid: initial; grid-area: initial; height: initial; hyphenate-character: initial; hyphenate-limit-chars: initial; hyphens: initial; image-orientation: initial; image-rendering: initial; initial-letter: initial; inline-size: initial; inset-block: initial; inset-inline: initial; interest-delay: initial; interpolate-size: initial; isolation: initial; left: initial; letter-spacing: initial; lighting-color: initial; line-break: initial; list-style: initial; margin-block: initial; margin: initial; margin-inline: initial; marker: initial; mask-type: initial; math-shift: initial; math-style: initial; max-block-size: initial; max-height: 100% !important; max-inline-size: initial; max-width: initial; min-block-size: initial; min-height: initial; min-inline-size: initial; min-width: initial; mix-blend-mode: initial; object-fit: initial; object-position: initial; object-view-box: initial; offset: initial; opacity: initial; order: initial; orphans: initial; outline: initial; outline-offset: initial; overflow-anchor: initial; overflow-block: initial; overflow-clip-margin: initial; overflow-inline: initial; overflow-wrap: initial; overflow: hidden; overlay: initial; overscroll-behavior-block: initial; overscroll-behavior-inline: initial; overscroll-behavior: initial; padding-block: initial; padding: initial; padding-inline: initial; page: initial; page-orientation: initial; paint-order: initial; perspective: initial; perspective-origin: initial; pointer-events: none !important; position-try: initial; position-visibility: initial; print-color-adjust: initial; quotes: initial; r: initial; reading-flow: initial; reading-order: initial; resize: initial; right: 0px !important; rotate: initial; ruby-align: initial; ruby-position: initial; rx: initial; ry: initial; scale: initial; scroll-behavior: initial; scroll-initial-target: initial; scroll-margin-block: initial; scroll-margin: initial; scroll-margin-inline: initial; scroll-marker-group: initial; scroll-padding-block: initial; scroll-padding: initial; scroll-padding-inline: initial; scroll-snap-align: initial; scroll-snap-stop: initial; scroll-snap-type: initial; scroll-target-group: initial; scroll-timeline: initial; scrollbar-color: initial; scrollbar-gutter: initial; scrollbar-width: initial; shape-image-threshold: initial; shape-margin: initial; shape-outside: initial; shape-rendering: initial; size: initial; speak: initial; stop-color: initial; stop-opacity: initial; stroke: initial; stroke-dasharray: initial; stroke-dashoffset: initial; stroke-linecap: initial; stroke-linejoin: initial; stroke-miterlimit: initial; stroke-opacity: initial; stroke-width: initial; tab-size: initial; table-layout: initial; text-align: initial; text-align-last: initial; text-anchor: initial; text-autospace: initial; text-box: initial; text-combine-upright: initial; text-decoration: initial; text-decoration-skip-ink: initial; text-emphasis: initial; text-emphasis-position: initial; text-indent: initial; text-overflow: initial; text-shadow: initial; text-transform: initial; text-underline-offset: initial; text-underline-position: initial; text-wrap: initial; timeline-scope: initial; top: 0px !important; touch-action: initial; transform: initial; transform-box: initial; transform-origin: initial; transform-style: initial; transition: initial; translate: initial; user-select: initial; vector-effect: initial; vertical-align: initial; view-timeline: initial; view-transition-class: initial; view-transition-group: initial; view-transition-name: initial; visibility: initial; border-spacing: initial; -webkit-box-align: initial; -webkit-box-decoration-break: initial; -webkit-box-direction: initial; -webkit-box-flex: initial; -webkit-box-ordinal-group: initial; -webkit-box-orient: initial; -webkit-box-pack: initial; -webkit-box-reflect: initial; -webkit-line-break: initial; -webkit-line-clamp: initial; -webkit-mask-box-image: initial; -webkit-rtl-ordering: initial; -webkit-ruby-position: initial; -webkit-tap-highlight-color: initial; -webkit-text-combine: initial; -webkit-text-decorations-in-effect: initial; -webkit-text-fill-color: initial; -webkit-text-security: initial; -webkit-text-stroke: initial; -webkit-user-drag: initial; white-space-collapse: initial; widows: initial; width: initial; will-change: initial; word-break: initial; word-spacing: initial; x: initial; y: initial; z-index: 2000000000 !important;"> <div class="intersub-ai-chat" style="color-scheme: initial; forced-color-adjust: initial; mask: initial; math-depth: initial; position: fixed !important; position-anchor: initial; text-size-adjust: initial; appearance: initial; color: initial; font: initial; font-palette: initial; font-synthesis: initial; position-area: initial; text-orientation: initial; text-rendering: initial; text-spacing-trim: initial; -webkit-font-smoothing: initial; -webkit-locale: initial; -webkit-text-orientation: initial; -webkit-writing-mode: initial; writing-mode: initial; zoom: initial; accent-color: initial; place-content: initial; place-items: initial; place-self: initial; alignment-baseline: initial; anchor-name: initial; anchor-scope: initial; animation-composition: initial; animation: initial; app-region: initial; aspect-ratio: initial; backdrop-filter: initial; backface-visibility: initial; background: initial; background-blend-mode: initial; baseline-shift: initial; baseline-source: initial; block-size: initial; border-block: initial; border: initial; border-radius: initial; border-collapse: initial; border-end-end-radius: initial; border-end-start-radius: initial; border-inline: initial; border-start-end-radius: initial; border-start-start-radius: initial; bottom: 0px !important; box-decoration-break: initial; box-shadow: initial; box-sizing: border-box; break-after: initial; break-before: initial; break-inside: initial; buffered-rendering: initial; caption-side: initial; caret-animation: initial; caret-color: initial; clear: initial; clip: initial; clip-path: initial; clip-rule: initial; color-interpolation: initial; color-interpolation-filters: initial; color-rendering: initial; columns: initial; column-fill: initial; gap: initial; column-rule: initial; column-span: initial; contain: initial; contain-intrinsic-block-size: initial; contain-intrinsic-size: initial; contain-intrinsic-inline-size: initial; container: initial; content: initial; content-visibility: initial; corner-shape: initial; corner-block-end-shape: initial; corner-block-start-shape: initial; counter-increment: initial; counter-reset: initial; counter-set: initial; cursor: initial; cx: initial; cy: initial; d: initial; display: flex !important; dominant-baseline: initial; dynamic-range-limit: initial; empty-cells: initial; field-sizing: initial; fill: initial; fill-opacity: initial; fill-rule: initial; filter: initial; flex: initial; flex-direction: column !important; flex-wrap: initial; float: initial; flood-color: initial; flood-opacity: initial; grid: initial; grid-area: initial; height: initial; hyphenate-character: initial; hyphenate-limit-chars: initial; hyphens: initial; image-orientation: initial; image-rendering: initial; initial-letter: initial; inline-size: initial; inset-block: initial; inset-inline: initial; interest-delay: initial; interpolate-size: initial; isolation: initial; left: initial; letter-spacing: initial; lighting-color: initial; line-break: initial; list-style: initial; margin-block: initial; margin: initial; margin-inline: initial; marker: initial; mask-type: initial; math-shift: initial; math-style: initial; max-block-size: initial; max-height: 100% !important; max-inline-size: initial; max-width: initial; min-block-size: initial; min-height: initial; min-inline-size: initial; min-width: initial; mix-blend-mode: initial; object-fit: initial; object-position: initial; object-view-box: initial; offset: initial; opacity: initial; order: initial; orphans: initial; outline: initial; outline-offset: initial; overflow-anchor: initial; overflow-block: initial; overflow-clip-margin: initial; overflow-inline: initial; overflow-wrap: initial; overflow: hidden; overlay: initial; overscroll-behavior-block: initial; overscroll-behavior-inline: initial; overscroll-behavior: initial; padding-block: initial; padding: initial; padding-inline: initial; page: initial; page-orientation: initial; paint-order: initial; perspective: initial; perspective-origin: initial; pointer-events: none !important; position-try: initial; position-visibility: initial; print-color-adjust: initial; quotes: initial; r: initial; reading-flow: initial; reading-order: initial; resize: initial; right: 0px !important; rotate: initial; ruby-align: initial; ruby-position: initial; rx: initial; ry: initial; scale: initial; scroll-behavior: initial; scroll-initial-target: initial; scroll-margin-block: initial; scroll-margin: initial; scroll-margin-inline: initial; scroll-marker-group: initial; scroll-padding-block: initial; scroll-padding: initial; scroll-padding-inline: initial; scroll-snap-align: initial; scroll-snap-stop: initial; scroll-snap-type: initial; scroll-target-group: initial; scroll-timeline: initial; scrollbar-color: initial; scrollbar-gutter: initial; scrollbar-width: initial; shape-image-threshold: initial; shape-margin: initial; shape-outside: initial; shape-rendering: initial; size: initial; speak: initial; stop-color: initial; stop-opacity: initial; stroke: initial; stroke-dasharray: initial; stroke-dashoffset: initial; stroke-linecap: initial; stroke-linejoin: initial; stroke-miterlimit: initial; stroke-opacity: initial; stroke-width: initial; tab-size: initial; table-layout: initial; text-align: initial; text-align-last: initial; text-anchor: initial; text-autospace: initial; text-box: initial; text-combine-upright: initial; text-decoration: initial; text-decoration-skip-ink: initial; text-emphasis: initial; text-emphasis-position: initial; text-indent: initial; text-overflow: initial; text-shadow: initial; text-transform: initial; text-underline-offset: initial; text-underline-position: initial; text-wrap: initial; timeline-scope: initial; top: 0px !important; touch-action: initial; transform: initial; transform-box: initial; transform-origin: initial; transform-style: initial; transition: initial; translate: initial; user-select: initial; vector-effect: initial; vertical-align: initial; view-timeline: initial; view-transition-class: initial; view-transition-group: initial; view-transition-name: initial; visibility: initial; border-spacing: initial; -webkit-box-align: initial; -webkit-box-decoration-break: initial; -webkit-box-direction: initial; -webkit-box-flex: initial; -webkit-box-ordinal-group: initial; -webkit-box-orient: initial; -webkit-box-pack: initial; -webkit-box-reflect: initial; -webkit-line-break: initial; -webkit-line-clamp: initial; -webkit-mask-box-image: initial; -webkit-rtl-ordering: initial; -webkit-ruby-position: initial; -webkit-tap-highlight-color: initial; -webkit-text-combine: initial; -webkit-text-decorations-in-effect: initial; -webkit-text-fill-color: initial; -webkit-text-security: initial; -webkit-text-stroke: initial; -webkit-user-drag: initial; white-space-collapse: initial; widows: initial; width: initial; will-change: initial; word-break: initial; word-spacing: initial; x: initial; y: initial; z-index: 2000000000 !important;">